Murder games [large type] : a thriller - Patterson, James, 1947-; Roughan, Howard (Little Brown & Company, 2017)
Dr. Dylan Reinhart wrote the book on criminal behavior. Literally--he's a renowned, bestselling Ivy League expert on the subject. When a copy of his book turns up at a gruesome murder scene--along with a threatening message from the killer--it looks like someone has been taking notes. Elizabeth Needham is the headstrong and brilliant NYPD Detective in charge of the case who recruits Dylan to help investigate another souvenir left at the scene--a playing card. Another murder, another card--and now Dylan suspects that the cards aren't a signature, they're a deadly hint--pointing directly toward the next victim. As tabloid headlines about the killer known as "The Dealer" scream from newsstands, New York City descends into panic. With the cops at a loss, it's up to Dylan to hunt down a serial killer unlike any the city has ever seen. Only someone with Dylan's expertise can hope to go inside the mind of a criminal and convince The Dealer to lay down his cards. But after thinking like a criminal--could Dylan become one?